From Ousia to Sophia: The Patristic and Classical Background to Twentieth-Century Essentialism and Personalism - Bouteneff, Peter C. (International journal of systematic theology, 2021)
Both Classical Greek philosophy and the early Christian theology that often drew upon it reflected a tension in their understanding of essence (οὐσία). Was it a concrete thing, something that could assume agency and be related to, or did it refer only to the shared characteristics that reflect things and persons of a common kind? In this article I first establish that this question pertains, mutatis mutandis, to the Platonic forms, as well as to Christian concepts of essence and nature. I then argue that the Christian theology of the conciliar period sided against the reification of essence/nature, noting that their misplaced concreteness resulted in problematic doctrines. In conclusion I briefly explore how this same dynamic plays out in twentieth-century Orthodox theology, as expressed by Sergius Bulgakov, Vladimir Lossky and John Zizioulas.